PEMBENTUKAN MODEL MANGSA PEMANGSA DENGAN PEMANENAN PADA PEMANGSA - Saiful Marom (Delta: Jurnal Ilmiah Pendidikan Matematika, 2013)
The Models of a predator prey with threshold harvesting on the predator is studied in this paper. In this article has established predator prey models with preydependent functions and the repon harvesting on predator assuming given.